Ta'lim al-khatt al-'Arabi wa tanmiyat maharatihi تعليم الخط العربي وتنمية مهاراته - الطويرقي, سامي بن عباد (Universitas Negeri Malang, 2024)
This study examines the teaching of Arabic calligraphy in Saudi Arabia by analyzing the theoretical and educational foundations of this essential skill, focusing on identifying the skills required for learning Arabic calligraphy, such as accurately drawing letters and words and organizing ideas according to writing rules. The study also explores the challenges facing calligraphy education, including the similarity of letters and difficulty in distinguishing between them, as well as the lack of emphasis on developing calligraphy skills by some teachers. It proposes improving the curriculum, providing specialized training programs for teachers, and developing objective assessment tools, thereby contributing to enhancing the cultural and educational identity of students.